PENGARUH PEMBELAJARAN BERWAWASAN LINGKUNGAN SEBAGAI SARANA MENINGKATKAN KECERDASAN NATURALIS PADA ANAK USIA 5-6 TAHUN DI TK PERTIWI KECAMATAN GUNUNGPATI SEMARANG - Ulfa, Dewi Maria (BELIA: Early Childhood Education Papers, 2014)
Naturalist intelligence is an ability that is associated with the knowledge to care,preserve and prevent environmental issues. The low of childrenâs awareness in the naturalist environment, as shown by the presence of a child who complained pet, pick flowers or damage the plant and has not been able to maintain their hygiene, themselves and the surrounding environment. Environmental Learning is a way to educate children through naturalist setup to create fun learning. The purpose of this study was to determine the environmental impact study or not on naturalist children aged 5-6 years. This research uses experimental quantitative research that is included true-Experimental Designs with Pretest-Posttest Control Group Design. The sampling was Purposive Random Sampling which states that the sampling is done at random. The test of t paired between pretest and posttest in experimental group produces the Sig 0,00 < 0.05 which means that there are significant differences between the controlgroup and the experimental group. Based on the value of 7,989> 1.714 indicates thatthere is a difference between the paired and pretest of the experimental group. The calculation results of t paired test between the pretest and posttest of experimental andcontrol groups indicates that there is significant difference because it has the Sig 0,00 <0.05 which means that there are significant differences between the control and experimental group. Based on the value of t count 4.437 > t table value, so that the 1,714 t count > t table, indicating that there is a difference between the results of the posttest of control group and the posttest of experimental group.Based on these results, the writer concludes that there are differences in the level of child naturalist intelligence in the experimental group before and after given environmental learning. Then it can be concluded that environmental learning gives effect in improving childrens naturalist intelligence and gives advice that the environmental learning can be developed as one way to improve childrens naturalist intelligence.